Teaching and Learning Strategy: Towards a Functional Approach to Didactics of the Arabic Language through the Book Linguistics and Didactics - ouchan, ali; omrani, idris (El Omda in Linguistics and Discourse Analysis, 2018)
Dr. Ali Ait Oushan is considered one of the emerging and brilliant figures who have made a strong mark in the field of pedagogical and didactic linguistics. Through his significant and distinguished research, works, and writings, he has opened new horizons that have enriched the Arabic linguistic library, without merely replicating or rehashing the contributions of his contemporaries striving for change and innovation. His approach is rooted in a theoretical framework guided by a deep engagement with modern Western theories and methodologies, addressing their complex questions and challenges, and employing them in a conscious and well-founded manner.